2004
DOI: 10.1207/s15327809jls1302_1
|View full text |Cite
|
Sign up to set email alerts
|

The Real Story Behind Story Problems: Effects of Representations on Quantitative Reasoning

Abstract: This article explores how differences in problem representations change both the performance and underlying cognitive processes of beginning algebra students engaged in quantitative reasoning. Contrary to beliefs held by practitioners and researchers in mathematics education, students were more successful solving simple algebra story problems than solving mathematically equivalent equations. Contrary to some views of situated cognition, this result is not simply a consequence of situated world knowledge facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
255
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(294 citation statements)
references
References 56 publications
18
255
1
9
Order By: Relevance
“…Studies have revealed that solving algebra word problems is challenging for the majority of students because the formal algebraic system creates a serious barrier to generating equations that represent the relationships within the problem (Kieran, 1992). However, students' challenges depend, not only on a formal algebraic system in the solution phase, but also on the linguistic form of the word problems in the comprehension phase (Koedinger & Nathan, 2004). Various researchers have proposed that solving algebra word problems consists of a "comprehension phase and [a] solution phase" (e.g., Cummins, Kintsch, Reusser, & Weimer, 1988;Mayer, 1982;Nathan, Kintsch, & Young, 1992).…”
Section: Student Performance In Solving Algebra Word Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that solving algebra word problems is challenging for the majority of students because the formal algebraic system creates a serious barrier to generating equations that represent the relationships within the problem (Kieran, 1992). However, students' challenges depend, not only on a formal algebraic system in the solution phase, but also on the linguistic form of the word problems in the comprehension phase (Koedinger & Nathan, 2004). Various researchers have proposed that solving algebra word problems consists of a "comprehension phase and [a] solution phase" (e.g., Cummins, Kintsch, Reusser, & Weimer, 1988;Mayer, 1982;Nathan, Kintsch, & Young, 1992).…”
Section: Student Performance In Solving Algebra Word Problemsmentioning
confidence: 99%
“…In the comprehension phase, a problem-solver comprehends and then forms the text base of the problem, utilizing words as an internal representation in his or her memory. In the solution phase, she or he expresses this internal representation externally and applies the rules of algebra to reach a conclusion (Koedinger & Nathan, 2004;Mayer, 1982).…”
Section: Student Performance In Solving Algebra Word Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…When asked to predict student performance, teachers and educators indicate that algebra story problems are harder for students to solve than matched symbolic equations, since students need to fi rst translate these word problems into symbolic notation (Nathan & Koedinger, 2000). Koedinger and Nathan (2004) compared students' performance on story problems and matched equations, and discovered that the assumed knowledge component analysis (e.g., that equations are needed to solve story problems) was incorrect. ey found that beginning algebra students are actually better able to solve introductory story and word problems than matched equations.…”
Section:   mentioning
confidence: 99%
“…One pedagogical approach that may further benefit student is to emphasize the different situations under which the two approaches are best suited. Although not specifically focused on the model method, previous research have shown that students are more successful when they use more concrete or grounded representations to solve simple algebra questions, but are more successful with more abstract, symbolic representations with more complex problems (Koedinger, Alibali, & Nathan, 2008;Koedinger & Nathan, 2004).…”
Section: Discussionmentioning
confidence: 99%